Brain Functional Connectivity and Power Spectrum Analyses during Mental Arithmetic (Jurnal Teknologi (Sciences & Engineering), 2015)
Mental calculation is one of the skills in executive function where problem solving skill and working memory were needed. The objectives of this study were to determine the directional connection of brain networks using partial directed coherence, and to observe the power spectrum of the brain rhythms during the mental task. Thirteen healthy participants were involved in the mental arithmetic task, where each participant was asked to subtract 1000 with number 7 continuously within 60 seconds. Electroencephalography machine was used to collect the data of brain signal, and the data were analyzed using partial directed coherence and Fast Fourier Transform. There were two possibilities that participants gave an answer; correct or incorrect answer to the calculation. As a result, regardless of correct or incorrect answer, mostly frontal and temporal area has been used in performing the mental task including some part of parietal area. Increasing theta frequency band and decreasing beta frequency band were involved in generating the information needed during mental arithmetic at the frontal area. It generates information of the mental calculation, which is send to other brain areas; i.e. centro-parieto-occipito-temporal area which show decreasing alpha frequency band; an indication of other cognitive processes. In conclusion, fronto-temporal area is activated during mental arithmetic task.